DETERMINASI FRAUD DALAM PENGELOLAAN LAPORAN KEUANGAN PADA AGEN MITRA CV SEKTOR AMDK DI KOTA SEMARANG - agnes ivena; Hayu Estrini, Dwi; Bebin Najmuddin, Ahmad (OIKOS: Jurnal Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2025)
This study aims to analyze the determinants of fraud potential in financial management by examining the influence of internal control systems and accounting information systems, with Anti-Fraud Awareness serving as a moderating variable. Integrating Agency Theory and the Fraud Triangle to support the observed phenomena among distribution agents of a bottled water (AMDK) company, this research employs a quantitative approach and a survey method. The population consists of 59 agents in Semarang, selected through purposive sampling based on the criteria of maintaining routine financial statements, with data analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results of the hypothesis testing indicate that both the internal control system and the accounting information system have a significant negative effect on fraud potential, suggesting that the effectiveness of these systems reduces the likelihood of fraudulent activities. Conversely, Anti-Fraud Awareness was found to have no direct influence on fraud potential. This study contributes to corporate management by providing insights into mitigating fraud risks through the reinforcement of internal control systems and the enhancement of accounting information transparency.